DEPOSITION AND PROPERTY CHARACTERISATION OF TaN COATINGS DEPOSITED WITH DIFFERENT NITROGEN CONTENTS - Gilberto Bejarano Gaitán; Aida Milena Echavarría García; Alix Caterine Quirama Ossa; Jaime Alberto Osorio Vélez (Revista EIA)
This study focused on the study of the influence of nitrogen content on the microstructure, chemical composition, mechanical and tribological properties of TaN coatings deposited on 420 stainless steel and silicon samples (100) using the magnetron sputtering technique. For the deposition of the TaN coatings an argon/nitrogen atmosphere was used, varying the nitrogen flux between 12% and 25%. For the coating characterization, scanning electron microscopy, energydispersive X-ray spectroscopy, atomic force microscopy, X-ray diffraction (XRD), micro-Raman spectroscopy, a microhardness tester, and a ball on disc tribometer were used. A refining of the columnar structure of the coatings, accompanied by a decrease in their thickness with the increased nitrogen content was observed. Initially, fcc-TaN (111) cubic phase growth was observed; this phase was changed to the fcc-TaN (200) above N2 12%. For contents greater than N2 18%, another nitrogen-rich phase was formed and the system tended towards amorphicity, particularly for a coating with N2 25% content. The TaN-1sample deposited with N2 12% in the gas mixture presented the highest micro-hardness value with 21.3GPa and the lowest friction coefficient and wear rate with 0.02 and 1.82x10-7 (mm³/Nm), respectively. From the obtained results, an important relationship between the microstructural, mechanical and tribological properties of the coated samples and their nitrogen content was observed.